Impact of combustion chamber wall heat loss on the energy, exergy, ecology, NOx emission based performance and multiobjective optimization of the precooled scimitar engine - Tanbay, Tayfun; Durmayaz, Ahmet (Pergamon-Elsevier Science Ltd, 2023)
In this paper, the impact of the combustion chamber wall heat loss on the performance of the hydrogen-fueled precooled combined cycle Scimitar engine is investigated. Overall and exergy efficiencies, coefficient of ecological performance and coefficient of emission based ecological performance (CEEP) are considered as the performance indicators to analyze the effects of wall heat loss flux, chamber length, chamber contraction area ratio, throat area and nozzle convergent half angle. A multiobjective optimization is carried out to find the optimum values of hydrogen and air mass flow rates, cruise speed and altitude and core nozzle outlet area. It is found that a wall heat loss flux of 10 MW/m2 decreases the overall efficiency by 1.1% and causes an increase of 2 kJ/gNOx in CEEP. Multiobjective optimization revealed that increasing the hydrogen mass flow rate, decreasing the cruise speed and air mass flow rate improve the overall performance while the optimum values of cruise altitude and core nozzle outlet area are 23 km and 4.94 m2, respectively. The optimized design has a 20.35% better emission performance than the base design with a compromise of a 3.38% reduction in the overall efficiency.& COPY; 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Multiobjective optimization; NO x emission; Wall heat loss; Combustion chamber; Hydrogen fuel; Scimitar engine; Variables